System performance of multislice spiral computed tomography. - Fuchs, T.O.J (IEEE Engineering in medicine and biology magazine)
Multislice spiral computed tomography (MSCT) is a technique that provides significantly improved image quality with drastically reduced scan times. Here, the authors describe the technological basics of multirow detector systems. Then they discuss the principle aspects of data processing and the resulting image quality for today's leading-edge MSCT systems, which offer rotation speeds up to 2 per second. The authors treat dose issues and finally present new applications that have become feasible with MSCT systems